Comparison of Laser Ablation and Solution‐Based ICP‐MS Results for Individual Foraminifer Mg/Ca and Sr/Ca Analyses. (10th December 2020) - Fehrenbacher, Jennifer; Marchitto, Thomas; Spero, Howard J.
Abstract: The trace element and isotopic composition of foraminifera shells are widely used in paleoceanography to reconstruct past ocean conditions. Individual foraminifer analysis (IFA) is a rapidly expanding technique for obtaining trace element and/or isotope data from individual foraminifer specimens. IFA permits an assessment of population variability, which can be linked to environmental conditions at the time of calcification or can be used to assess postdepositional diagenesis. Uniform interpretation of IFA depends on the assumption that the data are not impacted by analytical technique. Here, we compare paired trace element (Mg/Ca and Sr/Ca) data for the same specimens analyzed first using laser ablation inductively coupled plasma‐mass spectrometry (ICP‐MS), followed by solution ICP‐MS. Foraminiferal trace element (TE) to calcium ratios compare well between the two methods for foraminifera of simple morphology ( Orbulina universa ), heavily calcified specimens with TE‐homogeneous outer calcite ( Pulleniatina obliquiloculata ), or when all chambers in multichambered species are analyzed by the laser and averaged together ( Trilobatus sacculifer and Neogloboquadrina dutertrei ). We highlight potential issues in interpreting and comparing studies that use different analytical techniques and recommend that the paleoceanographic community establish accepted protocols for generating IFA that would maximize our ability to cross‐compare paleoceanographic data and reconstructions when different analytical techniques are used. Plain Language Summary: Foraminifera are sand‐grained sized marine protists that form a calcite shell. They are ubiquitous in the ocean, their shells are commonly found in ocean sediments, and they are widely used to reconstruct past ocean conditions. Advancements in analytical capabilities over the past 2 decades now allow researchers to conduct geochemical analyses on individual foraminifer shells, often referred to as individual foraminifer analysis or IFA. IFA differs from past techniques because it sheds light on seasonal and depth‐specific ocean conditions experienced by a population of individuals rather than average conditions when many shells are analyzed together. Here, we present data from two of the most commonly used procedures, laser ablation and solution analysis, to generate trace element data from the same individual shells in four foraminifera species and compare the results. We find that data from the two techniques compare well, but depend on shell morphology. For shells of simple morphology or those with heavily calcified outer calcite layers, either technique can be used and results can be readily cross compared. For foraminifera that have more complex morphologies, we suggest carefully designed sampling to ensure valid cross‐comparison between studies that use one or the other technique. Key Points: We compare laser ablation and solution‐based ICP‐MS Mg/Ca and Sr/Ca data generated on the same foraminifera shells Results show that both techniques yield comparable results, but depend on shell morphology and (for the laser analyses) the number of chambers analyzed We highlight potential issues in interpreting and comparing studies that use different analytical techniques